Ammonia toxicity in relation to lipid peroxidation - (:unkn) unknown (My University, 1998)
Even though several hypotheses about the toxic effects of ammonia on the central nervous system are proposed, the mechanism of action is not totally clear. In this study, in order to find out if the changes of the glutathione levels in the brain tissues are related with the antioxidant system and nitric oxide or not, 7.8 mmol/kg ammonium acetate and 45 mg/kg nitric oxide synthase inhibitor L-nitroarginine were applied i.p. acutely and chronically to 25-30 g mice. Acute and chronic administration of ammonia increased the lipid peroxide levels of brain and liver tissues of mice, but decreased the vitamin E and vitamin C levels. On the other hand it was found that L- nitroarginine prevented the increasing effects of acute and chronic administration of ammonia on lipid peroxide levels.